(3GdLhgQJjf GdYJjbJjf GdeGFYJjf ef GdUaQGA hGdHjVGAs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdNdb hHGSW GdQRb s
(3BNQgG (B:s
(3hGPG GYJQc GdOjfGQ eY GdOQGge aHjVI HSWM hdhf Ydi GdfGQ s
(3eUhQI Yf eNWhWI LGeYI CHSGdG HGdShjOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B229 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B409 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B35 s
Keywords: (3GdcjejGA h GdWHjYjGJs